Phytochemical constituents and pharmacological profile of aloe vera l. Plant: an overview - MANOJ KUMAR, (International Journal of Pharma and Bio Sciences, 2017)
Herbal medicines have been practiced since the ancient times to the present day. They are used to cure various infectious and non-infectious diseases. According to an estimate about 25% of medicines are derived from the plants. Aloe vera L. is a species of Aloe and has become a subject of interest because of its beneficial effects on human health. It belongs to the family Liliaceae and contains about 240 species. A. vera is an herb distributed throughout the world. It is used in Ayurvedic, Homeopathic and Allopathic streams of medicine. A. vera plant contains many potentially active phytochemical constituents viz. anthraquinones, vitamins, minerals, enzymes, sugars, fatty acids, hormones, amino acids, lignin and saponins. Several studies revealed some notable pharmacological profile of the A. vera plant such as antitumor activity, anti-inflammatory action, role in wound healing, cosmetic and skin protection application, moisturizing and antiaging agent, laxative effects, antidiabetic and hypolipidemic activity, immunomodulatory, antimicrobial, anti oxidative stress and many other medicinal uses.